2019
DOI: 10.1136/bmjopen-2019-031655
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the relationship between comorbidity and out-of-hospital cardiac arrest outcomes

Abstract: ObjectivesTo assess the current evidence on the effect pre-arrest comorbidity has on survival and neurological outcomes following out-of-hospital cardiac arrest (OHCA).DesignSystematic review according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses.Data sourcesMEDLINE, Ovid Embase, Scopus, CINAHL, Cochrane Library and MedNar were searched from inception to 31 December 2018.Eligibility criteriaStudies included if they examined the association between prearrest comorbidity and OHCA sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…These results are similar to other studies (e.g., an analysis of 40,000 patients from a 20-year registry found that patients with OHCA were more likely to have diabetes mellitus and myocardial infarction) (21). In addition, a systematic review analyzing the relationship between comorbidity and OHCA found that that prearrest comorbidities are associated with reduced survival and poorer neurological outcomes (22). Although the systematic review is limited by the high heterogeneity of the included studies, diabetes mellitus and myocardial infarction were especially demonstrated to be associated with poorer outcomes in OHCA patients.…”
Section: Discussionsupporting
confidence: 89%
“…These results are similar to other studies (e.g., an analysis of 40,000 patients from a 20-year registry found that patients with OHCA were more likely to have diabetes mellitus and myocardial infarction) (21). In addition, a systematic review analyzing the relationship between comorbidity and OHCA found that that prearrest comorbidities are associated with reduced survival and poorer neurological outcomes (22). Although the systematic review is limited by the high heterogeneity of the included studies, diabetes mellitus and myocardial infarction were especially demonstrated to be associated with poorer outcomes in OHCA patients.…”
Section: Discussionsupporting
confidence: 89%
“…The current study did not find significant differences between effects of comorbidities, including diabetes, hypertension, previous stroke, and liver disease, on survival of OHCA patients. A recent systemic review of 29 observational studies, attempted to find a relationship between pre-arrest comorbidity and outcomes of OHCA [ 34 ]. However, a meta-analysis was not performed in this review due to the clinical and statistical heterogeneity across the included studies.…”
Section: Discussionmentioning
confidence: 99%
“… 1 Outcomes of in-hospital cardiac arrest depend on many factors including the cause of the cardiac arrest 2 and arrest rhythm. 3 While studies have found a higher Charlson Comorbidity Index (CCI) or the presence of certain comorbidities such as diabetes and renal disease is associated with a higher mortality in out-of-hospital cardiac arrests, 4 , 5 few studies have looked at the effects of comorbidities on the outcomes of IHCAs. Here we study the association between the presence of a secondary diagnosis gastrointestinal bleeding (GIB) and the outcomes of IHCA using the National Inpatient Sample (NIS).…”
Section: Introductionmentioning
confidence: 99%